Change from Within? A Response to Ruth Armstrong's Article. (August 2014) - Bennett, Jamie
In her fascinating paper, Ruth Armstrong offers an appreciative account of the potential for trust and change in post-prison supervision and support. This transformative potential is seen not only in prisoners, or ex-prisoners, but also within the criminal justice system and those working within the system. In this response I focus on the issue of staff and occupational cultures, drawing upon both my own experience as a prison manager and my research into the working lives of prison managers. 1